RECESSION AND LIVING CONDITIONS OF NIGERIAN CIVIL SERVANTS, FOCUS IMO STATE CIVIL SERVANTS, 2016 TO 2020 - Amaefule , Eugene Amanze; Ugwa, Tochukwu Nonyelum (The Melting Pot, 2021)
This paper attempts a critical analysis of the effects of Recession on Living Conditions of Civil Servants in Nigeria with focus on Imo State. The study is earned out to identify the causes of recession in contemporary Nigeria and evaluate government efforts at ending or at least reducing recession to leverage on the living conditions of the masses. Using descriptive survey design, staff of five (5) ministries in Imo State Civil Service which constitute 7,163 formed population of study. The Taro Yamanes formula is adopted to determine the sample size which was calculated to be 379. The data collected from the respondents were later presented using simple percentages and tables. Hypotheses were tested using chi-square (χ2). The study concludes that the current economic recession in Nigeria has negative effects on government revenue, employment, income vulnerability, inflation, human health, crimes, infrastructural supply, family relations among others. The study therefore recommends that in order to make economic progress, Nigeria must change the structure of the economy, more away from oil to agriculture; value added entrepreneurship, chemicals, pharmaceutical industry, re-vitalize the iron and steel industries, revamp the machine tools industries for local fabrication of industrial tools. All these will change the structure of the economy to path of sustainable growth. Government and private sectors should partner to promote community based enterprises, innovation, markets, financial cooperatives among other things. Government should also encourage and promote modern agriculture for big and small farm holders, with modern facilities, provided.